Civics Learning Media Development For Fourth Graders of Primary School Based on Multimedia - Huda, Miftakhul Huda; Samsudi, Samsudi; Ahmadi, Farid (Educational Management, 2020)
Based on initial observation at fourth grade of Plalangan Pubic Primary School 04, through documentation, observation, and interview, it was found that the students’ civics learning outcomes were the lowest one. It was caused by lack of appropriate learning media to Civics lesson. Therefore, there is a need of multimedia based learning media by using flash macromedia with cultural material. This research aims to find out effectiveness of multimedia based learning media by using macromedia flash toward Civics learning outcomes at Primary School. This research and development used waterfall development method. The method consists of analysis, design, implementation, test, and maintenance. The findings showed that: learning multimedia by using macromedia flash with cultural material influenced cognitive learning outcomes as proven by differences of students’ understanding averages through t-test. It is shown by t count > t table (13.479 > 2.034) and Sig score 0.000 < 0.05 and average of gain score is 0.44 with moderate criterion. The conclusion tells that learning multimedia by using macromedia flash was effective to improve the fourth graders’ civics learning outcomes.